Кримінологічне забезпечення та супроводження деокупації тимчасово окупованної території України : дисертація - Луценко, Б. Г.; Lutsenko, B. H. (Харківський національний університет внутрішніх справ, 2024)
Дисертація присвячена комплексній характеристиці кримінологічного забезпечення і супроводження деокупації тимчасово окупованої території України. Запропоновано визначення деокупації тимчасово окупованої території України як стратегічний курс існування та розвитку українського суспільства та держави в умовах війни, основними цілями якого є припинення агресії російської федерації, усунення присутність її збройних сил та незаконних проксі-формувань на території України, силовий та інституціональний демонтаж окупаційних адміністрацій з одночасним відновленням правопорядку в межах міжнародно визнаних кордонів України на засадах українського законодавства, забезпечення безпеки громадян, запобігання кримінальним правопорушенням у перехідний період.

The thesis is focused on a comprehensive study of the criminological support and assistance in the de-occupation of the temporarily occupied territory of Ukraine. The author proposes to define the de-occupation of the temporarily occupied territory of Ukraine as a strategic course of existence and development of Ukrainian society and the State in the conditions of war, the main goals of which are to stop the aggression of the russian federation, eliminate the presence of its armed forces and illegal proxy formations on the territory of Ukraine, forcefully and institutionally dismantle the occupation administrations with simultaneous restoration of law and order within the internationally recognised borders of Ukraine on the basis of Ukrainian legislation, ensuring the security of citizens, and preventing criminal offences during the transition period.

Диссертация ориентирована на комплексное исследование криминологического обеспечения и содействия деоккупации временно оккупированной территории Украины. Автор предлагает определить деоккупацию временно оккупированной территории Украины как стратегический курс существования и развития украинского общества и государства в условиях войны, основными целями которого является прекращение агрессии Российской Федерации, ликвидировать присутствие своих вооруженных сил и незаконных марионеточных формирований на территории Украины, насильственно и институционально ликвидировать оккупационные администрации с одновременным восстановлением правопорядка в международно признанных границах Украины на основе украинского законодательства, обеспечивая безопасность граждан, а также предотвращение уголовных правонарушений в переходный период.
Criminological Support and Assistance in the De-occupation of the Temporarily Occupied Territory of Ukraine
Keywords: Україна; Дисертації. Theses. Диссертации; 081 – Право; злочинність; воєнно-агресивна злочинність; воєнний стан; кримінологічне забезпечення; тимчасово окуповані території України; деокупація; crime; counteraction to crime; hatred; resentment; violence; military-aggressive crime; crime prevention; aggression; war; martial law conditions; de-occupation; territory of Ukraine; criminological support; assistance; strategy; reduction of opportunities; protective space; mapping; criminal law; criminological legislation; criminal law policy; military service; collaboration; aiding and abetting the aggressor state; 12.00.08